2001
DOI: 10.1152/physiolgenomics.2001.6.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent expression of hypoxia-inducible factor-1α in renal medullary cells of rats

Abstract: Hypoxia-inducible factor-1alpha (HIF-1alpha) is a transcription factor that regulates the oxygen-dependent expression of a number of genes. This transcription factor may contribute to the abundant expression of many genes in renal medullary cells that function normally under hypoxic conditions. The present study was designed to determine the characteristics of HIF-1alpha cDNA cloned from the rat kidney and the expression profile of HIF-1alpha in different kidney regions and to explore the mechanism activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…After centrifugation of the homogenate at 6,000 g for 5 min at 4°C, the supernatant containing membrane and cytosolic components, termed homogenate, was divided into aliquots, frozen in liquid nitrogen, and stored at Ϫ80°C. Western blot analyses were performed as described previously (54). Briefly, protein samples (20 g) were subjected to 10% SDS-PAGE gel electrophoresis and electrophoretically transferred onto nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After centrifugation of the homogenate at 6,000 g for 5 min at 4°C, the supernatant containing membrane and cytosolic components, termed homogenate, was divided into aliquots, frozen in liquid nitrogen, and stored at Ϫ80°C. Western blot analyses were performed as described previously (54). Briefly, protein samples (20 g) were subjected to 10% SDS-PAGE gel electrophoresis and electrophoretically transferred onto nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that HIF-1␣ is abundantly expressed in renal medullary tissue (54). However, it remains unknown how the renal medullary HIF-1␣ levels are regulated in response to low PO 2 .…”
mentioning
confidence: 99%
“…When this occurs, renal cells initially respond with protective mechanisms that center around the phosphorylation of extracellular signal-regulated protein kinases 1 and 2 and the resulting stabilization of both HIF-1α and HIF-2α. [94][95][96]292,[323][324][325] These protective mechanisms include the up-regulation of pro-angiogenic factors such as isoform 164 of VEGF-A that protect against capillary rarefaction, and increased expression of matrix metalloproteinases that effect repair and protect against fibrosis by degrading extracellular matrix. 326,327 In addition, short-term exposure to hypoxia leads to increased renal expression of antioxidants such as nuclear factor erythroid 2-related factor 2, hemeoxygenase 1, and metallothionein I that protect against fibrosis and inflammation induced by reactive oxygen species.…”
Section: The Hypoxia Death Cyclementioning
confidence: 99%
“…Sophisticated counterbalance mechanisms help to restore renal oxygen homeostasis (49), and some researchers have proposed that HIF physiologically takes part in this fine-tuning network (50,51). However, evidence for HIF upregulation in normal kidneys is inconsistent (for review, see reference [6]).…”
Section: Stable Long-term Allografts Are Void Of Hif-1␣mentioning
confidence: 99%